Strategic Management of Waqf Assets Using the Community-Based Management (CBM) Method in the Waqf Institution of Malang - Dikuraisyin, Basar; Saoki, Saoki; Syihabuddin, Atok (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
This research aims to map the waqf asset management strategy at al-Khaibar waqf institution in Malang City. After mapping, it is analysed using the community-based management method. The selection of this method is based on the strategy pattern used by the institution by maximising the community, both managers, markets and partners. We know that until 2024 waqf assets are 2,171,041,349.74 M2 and only 23% are managed. Of the 23%, 71% are mosques, schools and cemeteries, waqf assets have not been able to be managed productively. Therefore, this research seeks to offer a solution to waqf asset management strategies in Malang City. This research is qualitative-descriptive. Data sources were obtained from interviews, and documentation to al-Khaibar waqf institution and BWI Malang City. The research findings show that: the steps of waqf asset development strategy management: 1) finding problems and problem identification; 2) Problem analysis is comprehensive ranging from material content, significance and risk; 3) action planning (class action) with three patterns; programme, risk and risk mitigation; 4) implementation of the term, which consists of short, medium and long term; 5) implementation of programmes at all levels; 6) evaluation is informal and formal. Second, the impacts are: 1) availability of business capital along with business facilities; 2) provision of business goods with qard al-hasan bi al-bay' contract; 3) productive work partners, making all MSMEs as business partners either as distributors, marketing, suppliers or volunteers.